The Binding Power of the Peace Agreement in the Event of a Breach of Contract - Ferdiansyah Putra Manggala; Ariel Alfito Catur Nanda (Inicio Legis Fakultas Hukum Universitas Trunojoyo Madura, 2026)
A peace deed is a legal instrument important for resolving civil disputes, especially defaults. A peace deed executed in a default lawsuit has executory power equal to a judge’s decision and can serve as a basis to request court execution if a party fails to fulfill obligations. This research aims to determine the peace deed’s binding power, legal protection for the aggrieved party, and remedies available for breaches. The method used is normative juridical with legislative and conceptual approaches. Although prior research exists on peace deeds, this study differs in its results. First, the peace deed is binding and final for the parties, as it is considered to have resolved the case and any potential related disputes, thereby precluding further legal remedies. Second, if a party violates the deed’s terms, legal protection may be sought internally through agreed sanctions or fines stipulated in the deed, or externally by filing an executory application consistent with the deed’s executory nature. Third, breaches of the deed can also be resolved by renewed mediation between the parties outside court to obtain an amicable solution. The findings highlight the deed’s dual role as both a settlement instrument and a basis for enforcement, while also emphasizing alternative dispute resolution when violations occur.